On the classification error rates in terms of semivariograms for Gaussian universal kriging models - Dučinskas, Kęstutis; Dreižienė, Lina (Lithuanian Journal of Statistics, 2021)
Bayes multiclass classification of spatial Gaussian data following the universal kriging model is considered. The closed-form expressions for the maximum likelihood (ML) estimator of regression parameters and the actual error rate (AER) in terms of semivariograms are derived.
Keywords: pairwise discriminant function; semivariogram; actual error rate